(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The study investigates the correlation between English proficiency and access to higher education, employment opportunities, and social mobility. It highlights the role of English as a medium of instruction in globalized education systems and its influence on interdisciplinary knowledge exchange. However, issues such as socio-economic disparities, lack of trained educators, and ineffective teaching methodologies hinder effective language acquisition. The study concludes with recommendations for curriculum improvements, teacher training programs, and policy reforms aimed at making English language education more accessible, inclusive, and impactful.